TIPS for the management of stomal variceal bleeding due to cirrhotic and non-cirrhotic portal hypertension - Kaczmarek, Dominik J.; Kupczyk, Patrick; Schultheiß, Michael; Chang, Johannes; Jansen, Christian; Trebicka, Jonel; Weismüller, Tobias; Vilz, Tim Oliver; Luu, Andreas Minh; Attenberger, Ulrike; Strassburg, Christian P.; Meyer, Carsten; Praktiknjo, Michael (Zeitschrift für Gastroenterologie, 2021)
Background Portal hypertension (PH) is associated with the development of esophageal or gastric varices, which can cause bleedings with high mortality. Varices can also manifest at sites of stomata. These parastomal varices can cause recurrent variceal bleedings (VB) despite local therapies. We present a case series of parastomal VB due to PH that were managed with implantation of transjugular intrahepatic portosystemic shunt (TIPS).Methods We retrospectively included all patients (pt) from 2 tertiary medical centers with parastomal VB between January 2014 and February 2020 who underwent the TIPS procedure. Results Nine pt were included. Seven pt had liver cirrhosis, mostly alcohol-related. Two pt had non-cirrhotic PH due to porto-sinusoidal vascular disease (PSD). Four pt had a colostomy, 1 an ileostomy, and 4 an ileal conduit. Malignancy was the leading cause of stoma surgery. All 9 pt suffered from recurrent parastomal VB despite non-selective beta-blocker and/or local therapy (e.g., compression, coagulation, suture ligation, or surgical stoma revision). All pt received TIPS implantation. In 7 pt, TIPS implantation led to sustainable hemostasis. Two pt suffered a bleeding relapse that was attributable to TIPS dysfunction. TIPS revision with coil embolization of the varices terminated the VB sustainably in both pt.Conclusions In pt presenting with recurrent stomal bleedings, parastomal varices as a rare complication of PH must be taken into consideration as an underlying cause. In our case series, we managed to sustainably cease parastomal VB by TIPS implantation with or without coil embolization of the ectopic varices.
Keywords: Zirrhose; Leber; portale Hypertonie; transjugulärer intrahepatischer portosystemischer Shunt; Varizenblutung